Structural serology of polyclonal antibody responses to mRNA-1273 and NVX-CoV2373 COVID-19 vaccines - Sandhya Bangaru; Abigail M. Jackson; Jeffrey Copps; Monica L. Fernández-Quintero; Jonathan L. Torres; Sara T. Richey; Bartek Nogal; Leigh M. Sewall; Alba Torrents de la Peña; Asma Rehman; Mimi Guebre-Xabier; Bethany Girard; et al. (Cell Reports)
Summary: Design and development of improved COVID-19 vaccines that can induce broad, durable immunity against emerging variants require an in-depth understanding of the antigenic and immunogenic properties of vaccines utilizing existing platforms. Here, we examine the antigenicity of two original COVID-19 vaccines by performing secondary analyses of the clinical trials for mRNA-1273 (this study was registered at ClinicalTrials.gov NCT04283461) and NVX-CoV2373 (this study was registered at ClinicalTrials.gov NCT04368988) using electron microscopy-based polyclonal epitope mapping (EMPEM). Both vaccines induce diverse polyclonal antibody (pAb) responses to the N-terminal domain (NTD) in addition to the receptor-binding domain of the Spike protein, with the NTD supersite being an immunodominant epitope. High-resolution cryo-EMPEM studies reveal extensive pAb responses to and around the supersite, with unique angles of approach and engagement. NTD supersite pAbs are also the most susceptible to variant mutations compared to other specificities, indicating that ongoing Spike ectodomain-based vaccine design strategies should consider immuno-masking this site to prevent induction of these strain-specific responses.